Association between Central Serous Chorioretinopathy and Risk of Depression: A Population-Based Cohort Study. (2nd May 2019) - Chen, Yu-Yen; Huang, Li-Ying; Liao, Wei-Ling; Chou, Pesus
Abstract : Purpose . To investigate the association between central serous chorioretinopathy (CSC) and the risk of developing depression. The risk factors associated with depression in CSC patients were also assessed. Methods . A population-based retrospective cohort study using the Taiwan National Health Insurance Research Database was conducted from the beginning of 2001 through the end of 2013. CSC patients and age- and gender-matched (1 : 4 matched) control subjects without CSC were enrolled in the study. Kaplan–Meier curves were generated to compare the cumulative hazard of subsequent depression between the CSC and control groups. A Cox regression analysis estimated the crude and adjusted hazard ratios (HRs) for depression. Risk factors leading to depression were investigated among the CSC patients. Results . 25, 939 CSC patients and 103, 756 controls were enrolled in the study. The CSC group had a significantly higher cumulative hazard for depression compared to the control group (p value < 0.0001). The Cox regression model indicated that the CSC group had a significantly higher risk for depression (adjusted HR = 1.33). Within the CSC group, significant risk factors for depression included age, female gender, low income, first-onset CSC, peptic ulcer, and smoking. The recent use of steroids prior to CSC, by all routes of administration, also significantly increased the risk for depression. However, treatment of CSC did not significantly reduce the risk for depression. Conclusion . Patients with CSC are at significantly greater risk of developing depression. Among CSC patients, age, female gender, low income, first-onset CSC, peptic ulcer, smoking, and recent use of steroids prior to CSC were significant risk factors for depression.